A LOVINGLY DANGEROUS DISEASE: GENDER DISCOURSE AND 19TH CENTURY MEDICINE - de Sousa, Sabrina Araujo; Favaro, Raiza Aparecida da Silva; Gregoleti, Anelisa Mota (ARACÊ, 2025)
During the 19th century, medical science produced a significant number of academic works in which the female body was the central theme. Theses and dissertations sought to prove female inferiority through physiology, under what became known as the "science of difference." These efforts led to an extensive cataloging of the female body. Physicians increasingly diagnosed pathologies originating in the female reproductive system and associated them with a supposedly sinful nature. Within this context, the physician Leopoldo Pires Porto presented the thesis On Intoxication by Love (1923), in which he medicalized emotions and treated love as a morbid affliction with distinct manifestations in men and women. The distinctions made by Pires Porto serve as a key source for this study, as they reflect gender differences during the 19th century and contribute to discussions about the scientific production of the period.